Pengaruh Kepercayaan Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Erigo Official Store Di Aplikasi Shoppe (Studi Pada Pengguna Shoppe Di Institut Ilmu Sosial Dan Manajemen STIAMI) - Amirullah, Yuhan; Santoso, Teguh (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Consumer satisfaction is influenced by several factors such as trust and service quality. Some of the phenomena that exist in the Erigo Official Shop on the Shopee Application are customer complaints that are so high regarding the quality of service and also prefer to the trust of the customers themselves that there are many bad reviews in the rating column on the Erigo Official Shop itself. This research aims to determine the effect of trust and service quality on customer satisfaction at the Erigo Official Shop on the Shopee Application. The research method used in this research is a quantitative approach and the respondents in this research are STIAMI Institute students who have shopped at the Erigo Official Shop on the Shopee Application. The data collection technique used was a questionnaire, with a sample size of 110 students. Data quality techniques use validity tests and reliability tests. Test data analysis using multiple linear regression. The results of this research prove that there is a positive and significant influence of trust and service quality on customer satisfaction. Partially, trust contributed 51.7% and service quality contributed 49.4%. Trust and service quality simultaneously influence purchasing decisions by 64% and the remaining 36% is influenced by other variables.